Preliminary Modelling of the Permeability Reduction in the Injection Zone at Berlin Geothermal Field, El Salvador - Portier, Sandrine; Vuataz, François; Barrios Martinez, Antonina Luz; Siddiqi, Gunter (My University, 2010)
The exploitation of the Berlin geothermal field (El Salvador) started in February 1992 with two 5 MW electrical units. In December 1999, exploitation at a larger scale started with the operation of two turbo-generating condensation units of 27.5 MWe each. Since the beginning of exploitation until today, all the deep thermal fluids produced during the generation of electricity have been injected back to the reservoir. However, the well injectivities declined because of self-sealing processes of fracture thereby reducing permeability in the injection zones.
Our study focuses on the factors that may have caused the observed loss of injectivity of reinjection wells, using numerical simulation of fluid flow with coupled chemical reaction modelling. Such a model helps quantitatively understand the complex interplay of thermal, hydraulic and chemical processes (THC) and to predict the impact of reinjection on reservoir properties. The first preliminary simulation was carried out with FRACHEM code. This paper presents simulation results that reproduce in some way the observed decrease of permeability in the injection zone with time.
Keywords: Geothermal reservoir; injectivity; silica scaling; thermo-hydraulic-chemical coupled code; water-rock interactions; permeability; reinjection well; Berlin geothermal field; El Salvador